PERUBAHAN GAYA HIDUP MAHASISWA FAKULTAS EKONOMI UNIVERSITAS RIAU ASAL KECAMATAN KANDIS SEBELUM DAN SESUDAH TINGGAL DI KOTA PEKANBARU - Enggraini, Irma Rizki; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Lifestyle is something that is beyond the personality. Lifestyle happens especially in the Faculty of Economics is of respondents noticed a significant change from other Faculties, starting from the change in the dress code that is used by students and staffs who work in that environment. The use of private vehicles ranging from motorcycles and cars that look more numerous than in other Faculties, the use of communication devices such as mobile phones (HP) more updates. With a style of life lived now makes students lose Reviews their critical mind. The purpose of the formulation of the problem is to know the shapes of the lifestyle of students of Faculty of Economics, University of Riau after staying in Pekanbaru and to determine the factors of lifestyle changes that occur in students of the Faculty of Economics, University of Riau. Types of change lifestyle from the students are influenced by advertising a lifestyle, an independent lifestyle, hedonistic lifestyle and their consumer behavior which students inculcate the importance of self-image to appear publicly in advance. Factors affecting changes in economic students of Faculties of this is the influence of attitude, personality, self-concept, motives, perceptions, social class and family. With the problems and objectives that have been Formulated, then the population in this study were all students of economic university Faculties Riau originating from Kandis District using census method or the total amounting to 31 students. This research Data collection instrument was a questionnaire and documentation. In analyzing the data is using quantitative descriptive method. The conclusion of this research is a form of lifestyle changes that occur in the Student Faculty is dominant in the form of an independent lifestyle changes which these students to find out the latest information via various electronic media. Second, the factors that influence a positive impact, the family does not limit the space for them to undergo training, education gained influence them to become people of character, style according to Socioeconomic circumstances, and they reviews also make friends with people who can provide comfort to them in any case.Keywords: Changes, Lifestyle, Students